(untitled) (Journal of Tikapur Multiple Campus, 2022)
This article assesses the women literacy and health outcome inequality in Nepal. The study attempted to assess the nexus between women literacy and some key health outcomes based on provincial level data of Nepal. Basically the study follows the descriptive analysis with explanatory design under quantitative research based on the secondary data from ministry of health and population of Nepal (2017). Statistical analysis of provincial wise key health outcome data was done using chi-squire test of the goodness of fit to ensure evidence of inequality of the health outcome across the provinces of Nepal. Likewise, to find the causal relationship between women literacy rate (WLR) and institutional delivery rate (ID), contraceptive prevalence among married women (CPMW), child immunization rate (CIR), ANC (Antenatal Care) service receive by women (ANCRW), teenage pregnancy rate (TPR), total fertility rate (TFR) in seven provinces was observed using correlation and regression analysis tool. The result of chi-square test shows that there could be observed inequality in WLR and ID. Likewise, correlation analysis shows that there is positive correlation between WLR and ID, WLR and CPMW, and WLR and ANCRW but there is negative relation between WLR and CIR, WLR and TPR, WLR and TFR. The regression analysis shows that there is significant relationship among the variables WLR and ID, ANCRW, TPR, TFR. Therefore, it can be concluded that it is essential to increase women literacy to bring improvement in aforementioned key health outcomes. The implication of the study will help to make effective public health policy and strategy to reduce the equity gaps in health outcomes in Nepal.